La importancia del uso de las aplicaciones digitales para la protección de nuestros datos personales. - Plaza Zapata, Steeven Enrique (2022)
Data in our current context and probably without realizing it has become one of the most important assets of this century, it has become a currency for many aspects, and it is also a key to access and power, for which, the main objective of this research, is to analyze the importance of our data and the use of digital applications to protect them, since it is necessary to know that our data has always been valuable, and by interpreting it, we obtain knowledge, and knowledge is an analogy to power, for which it is a priority, given the low popularity of the topic, to know how to protect our data. The methodology used in this research was a non-experimental design, to obtain information the bibliographic method was used, and to process and study the information, the analytical method was used. According to the analysis carried out, it is concluded that, since they began to collect data from citizens, and discovered that by analyzing it, they could obtain valuable information, personal data has become a very important asset, granting power to those who possess it, currently, they collect our personal data all the time, immersed in surveillance, traffic with our data and we do not know exactly how companies use them, becoming a lacerating asset for us, however, we can still take care of our data since there are alternatives for its protection.